Rectovaginal Fistula of Different Etiologies: Clinical Case Reports - Mitra, P; Mukherjee, S; Hassan, H; Soreng, PS; Adhikari, S; Roy, TK (Nepal Journal of Obstetrics and Gynaecology, 2014)
We report three cases of recto vaginal fistula (RVF) due to different etiologies. First case was due to sexual trauma (vaginal intercourse) which is not very common. The second case was due to obstetric trauma (the most common etiology of RVF) and the third case was caused by chronic lower genito-urinary infection in a HIV positive lady. We have included the successful surgical procedures of first two cases. But the repairing of the third case was failed hence planned to operate after six months. DOI: http://www.dx.doi.org/10.3126/njog.v7i2.11143 Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 2 / Issue 14 / July-Dec, 2012 / 43-46